2018
DOI: 10.1016/j.ymssp.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining manufactured geometries of deep-drawn components through a model updating procedure using geometric shape parameters

Abstract: The vibration response of a component or system can be predicted using the finite element method after ensuring numerical models represent realistic behaviour of the actual system under study. One of the methods to build high-fidelity finite element models is through a model updating procedure. In this work, a novel model updating method of deep-drawn components is demonstrated. Since the component is manufactured with a high draw ratio, significant deviations in both profile and thickness distributions occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The resulting MAC matrix is plotted in Figure 5 where a perfect correlation is observed for the first 5 modes, with the accuracy decreasing toward higher frequencies. These results are in agreement with those reported using the traditional FEM approach in [67], where a similar accuracy is obtained.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The resulting MAC matrix is plotted in Figure 5 where a perfect correlation is observed for the first 5 modes, with the accuracy decreasing toward higher frequencies. These results are in agreement with those reported using the traditional FEM approach in [67], where a similar accuracy is obtained.…”
Section: Resultssupporting
confidence: 92%
“…The first component considered is an oil-pan look-alike structure that has been employed in previous studies in order to understand the vibration and noise radiation characteristics of this type of components [67,68]. In fact, the radiated noise coming from an oil-pan can have a significant contribution towards the total noise emitted by an automobile engine and it was shown in the literature that oil-pan noise reduction up to 1.5 dB(A) can be achieved by structural optimization [69,70] or through resorting to passive damping treatments.…”
Section: Componentmentioning
confidence: 99%
“…Therefore, the implementation of design by the morphing approach provides time and cost savings for the optimum design outlines for alloy wheel design procedures. 34 Morphing is implemented on the FEM to create the corresponding shape variables. Data were collected using the Latin hypercube and Hammersley methods by considering six design parameters with long computation times for each analysis.…”
Section: Design Of Experiments Analysis To Collect the Data Setmentioning
confidence: 99%
“…Dev et al [17] carried out a modal analysis of an oil pan using the geometry obtained from forming simulation results. Balla et al [18] showed that significant changes in the geometry profile and thickness distribution occurred in the single-stage deep-drawn components. They demonstrated that the mode shapes of the physical parts are significantly altered when compared to the base CAD finite element model results.…”
Section: Vibro-acoustic Variabilitymentioning
confidence: 99%